2013
DOI: 10.3892/ol.2013.1389
|View full text |Cite
|
Sign up to set email alerts
|

Sonoporation by low-frequency and low-power ultrasound enhances chemotherapeutic efficacy in prostate cancer cells in vitro

Abstract: Combination therapy is used to optimize anticancer efficacy and reduce the toxicity and side-effects of drugs upon systemic administration. Ultrasound (US) combined with micro-bubbles (UM) enhances the intracellular uptake of cytotoxic drugs by tumor cells, particularly drug-resistant cells. In the present study, low-frequency and low-energy US (US irradiation conditions: frequency, 21 kHz; power density, 0.113 W/cm2; exposure time, 2 min at a duty cycle of 70%; and valid treatment time, 84 sec) were used in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…However, a large percent of androgen-dependent cancers will gradually become resistant to castration, i.e., castration-resistant prostate cancer (CRPC) (2). At this stage, second-line endocrine therapy and chemotherapy should be administered (3). Docetaxel (DTX) is a clinically approved drug for the treatment of various metastatic CRPCs (4).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a large percent of androgen-dependent cancers will gradually become resistant to castration, i.e., castration-resistant prostate cancer (CRPC) (2). At this stage, second-line endocrine therapy and chemotherapy should be administered (3). Docetaxel (DTX) is a clinically approved drug for the treatment of various metastatic CRPCs (4).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DTX has been reported to exert antiangiogenic effects (7). However, the systemic administration of DTX exposes all tissues to cytotoxic drugs (3). This side-effects of systemic chemotherapy highlights the requirement for improved and targeted delivery to aid in increased localized drug uptake in the targeted cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasound has been widely used in cancer therapy and has been shown to mediate apoptosis through thermal, cavitation, sonoporation and sonochemical effects; however, the underlying mechanisms remain unclear (5). Furthermore, a number of experiments indicated that the effects of ultrasound may be enhanced by microbubbles (6,7).…”
Section: Introductionmentioning
confidence: 99%